2021
DOI: 10.1021/acs.analchem.0c04561
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Self-Assembly of a Close-Packed Gold Octahedra Array for SERS Sensing Exosomal MicroRNAs

Abstract: MicroRNAs (miRNAs) in exosomes can be transferred from parental cells to recipient cells by trafficking exosomes, and they are effective in regulating the gene expression of the recipient cells. Therefore, exosomal miRNAs play a vital role in cancer biology and could be potential biomarkers for cancer diagnosis and therapeutic responses. However, accurate detection of exosomal miRNAs is still challenging due to the low abundance of any given miRNA in exosomes. Herein, a surface-enhanced Raman scattering (SERS)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
41
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(42 citation statements)
references
References 51 publications
0
41
0
Order By: Relevance
“…Zhang et al achieved controlled self-assembly of gold nanoparticles into a 3D hotspot structure by regulating the addition of halogen ions [ 64 ]. Kang et al implemented a bottom-up approach to achieve self-assembly of a close-packed gold octahedral array that exhibited an intense electric field at the edges and sharp corners of the nanostructure [ 65 ]. Ye et al fabricated densely-packed, 2D arrays of plasmonic nanoparticles via nanoparticle self-assembly at the water-oil interface [ 66 ].…”
Section: Applications Of Sers In Drug Detectionmentioning
confidence: 99%
“…Zhang et al achieved controlled self-assembly of gold nanoparticles into a 3D hotspot structure by regulating the addition of halogen ions [ 64 ]. Kang et al implemented a bottom-up approach to achieve self-assembly of a close-packed gold octahedral array that exhibited an intense electric field at the edges and sharp corners of the nanostructure [ 65 ]. Ye et al fabricated densely-packed, 2D arrays of plasmonic nanoparticles via nanoparticle self-assembly at the water-oil interface [ 66 ].…”
Section: Applications Of Sers In Drug Detectionmentioning
confidence: 99%
“…Where the gold octahedra in the array stand uniformly on their triangular faces, significantly improving detection sensitivity and uniformity. This model enables let-7a detection with single-base specificity in the presence of a target by detecting the SERS intensity change caused by the conversion of DNA from a hairpin structure to a double-stranded body ( Kang et al, 2021 ). Chen et al (2020) A novel exosome/metal nanohybrid was constructed.…”
Section: Sers Technology For Exosome Detectionmentioning
confidence: 99%
“…Remarkable biosensing performance can be obtained by using 2D highly packed lattices of polyhedral nanoparticles although their EF SERS values are lower than that achieved with 3D architectures. Kang et al [132] reported a novel and highperformance SERS-based sensing platform for a quantitative measurement of let-7a miRNAs in MCF-7 exosomes. The substrate consisted of an array of close-packed and ordered Au octahedra (Figure 10a-1), whose sharp edges are ideal for SERS enhancement.…”
Section: Sers-based Biosensingmentioning
confidence: 99%
“…Adapted with permission. [132] Copyright 2021, American Chemical Society. b-1) Working scheme of the Au-Ag nanorod SERS platform (top panel) and SEM images before (bottom-left panel) and after (bottom-right panel) the modification with Au, b-2) Raman spectra of human IgGs on different SERS substates, and b-3) calibration curve for the detection of human IgGs obtained by evaluating the Raman intensity at 1080 cm −1 .…”
Section: Seira-based Biosensingmentioning
confidence: 99%
See 1 more Smart Citation